Effect of theoretical biomechanics on open jump the platform jumps performance using jumps (vault) in artistic gymnastics - Hassan, H. S.; Hanna, S. J.; Ameen, F. M. (Journal of Human Sport & Exercise, 2015)
The biomechanics is an important science the physical education, thereby sports analyzed and thereafter correct the technical errors. Gymnastics is more related with biomechanics than other sports, this science contribute in the analysis, illustration, understanding, and improvement of sports technique. This study aimed to identify the effectiveness of theoretical information on the Platform Jumps (Vault) Performance, and to identify the difference of the performance level between pre-test and post-test. This research hypothesized significant differences in each of the theoretical biomechanics information in open jump on the platform jumps (Vault) performance between pre-test and post-test. An experiment used quasi experimental design, the population included 40 female undergraduate students in the physical education college, University of Diyala- Iraq during 2012-2013 divided into equal two groups. The biomechanics theoretical information that given to the students impacted on their skill and performance positively. Increase the level of Gymnastics performance of open jump on the platform for the female students.